2012
DOI: 10.1111/j.1360-0443.2012.03941.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective memory and future event simulation in individuals with alcohol dependence

Abstract: 1 OVERVIEWThis major research project focuses on the possible influence that chronic substance use may have on prospective memory (PM) ability.Part one consists of a literature review examining the associations between recreational substance use and impairments in PM. This identifies 24 studies from 23 publications examining PM ability in recreational substance users. Although PM impairments are reported by most, the review highlights a number of methodological weaknesses in the existing body of research. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 69 publications
4
61
1
Order By: Relevance
“…For both strategy-based PM training types, we observed a significant increase in PM accuracy in terms of PM cue detection as well as in accuracy of PM intention retrieval from pretest to posttest. For imagery training, this is in line with prior single-session PM training studies targeting PM intention encoding that showed training-related enhancements in PM accuracy in terms of PM cue detection [5, 15, 17-19] (there are no prior PM training studies targeting the intention-retention phase). Notably, our study is the first in comparing 2 strategies targeting different PM phases and their inherent cognitive processes.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…For both strategy-based PM training types, we observed a significant increase in PM accuracy in terms of PM cue detection as well as in accuracy of PM intention retrieval from pretest to posttest. For imagery training, this is in line with prior single-session PM training studies targeting PM intention encoding that showed training-related enhancements in PM accuracy in terms of PM cue detection [5, 15, 17-19] (there are no prior PM training studies targeting the intention-retention phase). Notably, our study is the first in comparing 2 strategies targeting different PM phases and their inherent cognitive processes.…”
Section: Discussionsupporting
confidence: 81%
“…Evidence suggests that EFT can successfully support PM performance. In a study by Griffiths et al [17], imagining future events increased social drinkers’ time-based PM performance in a Virtual Week task (but did not improve PM performance of alcohol dependent participants). McFarland and Glisky [18] reported a significant increase in PM performance for an imagery-based EFT strategy and an implementation intentions strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic alcohol use and dependency is associated with impaired cognitive functioning particularly working memory, visuospatial abilities and prospective memory, as well as with mental health problems (Norton and Halay, 2011;Bernardin et al, 2014;Sullivan et al, 2000;Fox et al, 2000;Oscar-Berman and Marinkovic, 2007;Ratti et al 2002;Griffiths et al, 2012). That alcohol gel users also display poorer performance in these areas is therefore consistent with this previous research.…”
Section: Discussionsupporting
confidence: 83%
“…In addition, visuo-spatial abilities are also impaired (e.g. 7 memory and visual learning, visuospatial organisation, visuospatial processing; Oscar- Berman and Marinkovic, 2007;Ratti et al 2002) and more recent evidence documents prospective memory deficits (PM; remembering to do something at some point in the future Griffiths et al, 2012), which along with retrospective memory (RM; the learning retention and retrieval of events, words and people encountered or experienced in the past (Smith et al, 2000;Soderlund et al, 2007) has also been shown to be disrupted in chronic and/or excessive alcohol users (Heffernan, 2008). In addition to cognitive functioning, chronic exposure to ethyl-alcohol has also been frequently associated with mental health problems such as anxiety and depression (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Executive and amnestic problems, including prospective memory, have received particular attention, as they are linked to treatment outcomes and maintenance of abstinence (Le Berre et al, 2010;Fish, Wilson & Manly, 2010, Montgomery, Ashmore & Jansari, 2011Griffiths et al, 2012;Lyu & Lee, 2012). Despite this, literature remains inconclusive on their extent and clinical relevance.…”
Section: Why Is Neurocognitive Evaluation In Alcohol Use Disorders Somentioning
confidence: 99%